Social Support and Substance Abuse Relapse - Sari, Adelia Perwita; Wahyuni, Chatarina Umbul; Wibowo, Arief (Health Notions, 2018)
Substance abuse is the health problem that affects physical, mental and social health. Rehabilitation program is one of the strategies to reduce the number of addictive substance users but the relapse is common happen to the users that taking rehabilitation. The aim of this study was to assess social support as risk factors for substance abuse relapse. This case-control study was conducted to 39 people in each control and case group. The samples were obtained with simple random sampling. The cases were the person who relapses after completed rehabilitation program, while the controls were the person who still being abstinence after completed rehabilitation program. Data were collected with the questionnaire and analyzed with Chi-square test. The result showed that social support was related to substance abuse relapse (p=0,000). The lack of social support was related to the higher risk of substance abuse relapse (OR=6.92, 95%CI=2.51 â 19.22). The appraisal support was the dominance risk factor  (OR=10.88, 95%CI=3.48 - 33.98) of substance abuse relapse compared to informational, instrumental, and emotional support. The involvement of the source of social support in rehabilitation program is important to help the users stay abstinence  after released from the rehabilitation center.